The Future of Work in Asia and Beyond: A Technological Revolution or Evolution?, 1st edition - Nankervis, Alan R. (Routledge, 2020)
The Future of Work in Asia and Beyond presents the findings and associated implications arising from a collaborative research study conducted on the potential impact of the Fourth Industrial Revolution (4IR – or Industry 4.0) on the labour markets, occupations and associated future workforce competencies and skills across ten countries.